A contribuição da história para educação ambiental em comunidades - Festozo, Marina Battistetti [UNESP]; Tozoni-Reis, Marília Freitas de Campos [UNESP] (My University, 2010)
The relationship between human beings and between them and nature are the result of a historical and social context in which they are inserted. The man is a natural living being who can only survive by the exchange with nature’s metabolism, but over time and human’s decisions this relation was interrupted, which strengthened by capitalism logic resulted as a civilization crisis. With these concerns, it’s necessary to overcome the context in which the crisis was generated, transforming the relationship between men and nature. This study, based on Critical Environmental Education and qualitative research methodology, occurred on a seashore community on Guarujá, investigated the the involvement of its population on social activities already developed on Prainha Branca: how they exercise their community citizenship, which factors limit these processes, and how responsible the residents feel about their own reality, in order to elucidate the aspects that involve that dynamics and population’s potential to build their own history.

As relações estabelecidas entre seres humanos e entre eles e a natureza são fruto de um contexto histórico e social em que estão inseridos. O homem é um ser natural vivo, que só pode sobreviver através de seu intercâmbio com o metabolismo da natureza, contudo ao longo do tempo e das decisões humanas este vínculo intercambial foi rompido, o que reforçado pela lógica capitalista resultou em uma crise civilizatória. Com estas preocupações, vê-se a necessidade de superar o contexto em que a crise foi gerada, através da transformação do relacionamento entre homens e natureza. Este estudo, a partir dos pressupostos da Educação Ambiental crítica e metodologia de pesquisa qualitativa, realizou-se em uma comunidade caiçara do Guarujá e buscou investigar o envolvimento da população nas atividades sociais desenvolvidas na Prainha Branca: como se dá o exercício da cidadania comunitária, os fatores que limitam estes processos, e o quão responsáveis os moradores se sentem pela configuração de sua própria realidade, de modo a elucidar os aspectos que envolvem esta dinâmica e a potencialidade da população de construir sua própria história.
Keywords: Communities; History; Social organization; Educação ambiental; Comunidades; História; Organização social